HUBUNGAN FEAR OF MISSING OUT (FOMO) DENGAN MINAT BELAJAR PJOK SISWA KELAS X SMK NEGERI 6 SEMARANG - Maulana Faqihnafidin; Melani Fajar Fatatul Ulum; M. Bayu Nurdiansyah (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study was motivated by the increasing use of social media among adolescents, which may lead to Fear of Missing Out (FoMO) and is assumed to be related to students’ learning interest. The purpose of this study was to examine the relationship between FoMO and students’ learning interest in Physical Education, Sports, and Health among tenth-grade students at SMK Negeri 6 Semarang. This study used a quantitative approach with a descriptive correlational method. The sample consisted of 66 tenth-grade students from classes X BUS 1 and X PH 3. The research instruments were FoMO and Physical Education learning interest questionnaires using a Likert scale. The data were analyzed using descriptive statistics and Pearson Product Moment correlation through IBM SPSS Statistics. The results showed that students’ FoMO level was predominantly in the moderate category, while their learning interest in Physical Education was mostly in the fairly good category. The correlation test showed a very weak positive and non-significant relationship between FoMO and learning interest. Therefore, FoMO cannot be considered the main factor explaining students’ learning interest in Physical Education. Students’ learning interest may be more influenced by learning conditions, classroom environment, teacher support, peer interaction, and comfort during physical activities.